Clocking in Modern VLSI Systems - Xanthopoulos, Thucydides (Integrated Circuits and Systems, 2009)
Clocking in Modern VLSI Systems covers a wide range of subjects related to microprocessor clocking including distribution, flop design, inductive techniques, phase noise and jitter, delay lock techniques, resiliency and other techniques to address process variation and physical design aspects. The book contains rigorous analytical treatment for a number of important topics such as timing uncertainty due statistical spatial and temporal phenomena, metastability, jitter in the time and frequency domain and supply-induced clock noise. It also contains a large number of design examples and case studies, background information, a complete list of references and a number of advanced topics. The subjects covered reflect to a large extent the collective interests and foci of both industry and academia with respect to clocking. It is very up-to-date and co-authored by a panel of industry experts involved in clock design in major processor chips. Clocking in Modern VLSI Systems is authored from a strong design perspective and will help readers interested in clock design obtain the necessary background information and tools for such a task. The book also captures design trends that have appeared over the last few years and provides a comprehensive list of references for further study.